A DEIXIS STUDY OF SONG LYRICS "AT MY WORST" (PROJECT (Professional Journal of English Education), 2023)
The purpose of this research was to decide the deixis expression contained in “At My Worst” song lyrics by Pink Sweats. Type of deixis available are personal deixis, spatial deixis, temporal deixis, social deixis, and discourse deixis. The researcher has chosen “At My Worst” by Pink Sweat as the object analysis, because this song is going viral, especially on the TikTok application. The descriptive qualitative method was used by the writer to determine the type of deixis in the content. As concerns to the results of the research, it can be found that knowing the deixis words in the chosen song lyrics will assist all those who listen and read the song will have the best agreement and the stage of the song will achieve the listeners. The researcher found the result of deixis in this study is person deixis showed dominant, with the value 50 frequency, and followed by spatial and social deixis has 2 frequency each, temporal deixis has 5 frequency, and discourse deixis with only one frequency. Keywords:  Deixis; Song Lyrics